The Face of the War in Ukraine. War Devastation and Reconstruction Concepts - Belinskyi, Serhii; Dmytrenko, Andrii; Ivashko, Yulia; Pawłowska, Aneta (Narzędzia wojny, 2023)
Every war brings losses not only on the economic level but also on the social level. Russia's aggression against Ukraine, which began on 24 February 2022, made this clear once again. A country that had already experienced many starts in historical times also found itself in the heat of battle this time. The military conflict led to a significant migration of the Ukrainian population. As a result of bombing and shelling by the Russian army, many buildings of various purposes were destroyed – not only those classified as military infrastructure or those under state administration, schools, hospitals, residential buildings, businesses but also places of worship – orthodox churches. Although the war is still ongoing, gradual reconstruction is already taking place in the liberated territories and revitalization programs are being developed. Many ideas related to reconstruction are borrowed from the experience of Poland and its reconstruction after the devastation of World War II.The article aims, among other things, to draw the attention of the world public to the war drama unfolding in Ukraine and to show the destruction from the first phase of the war as documented by a military photographer from the 28th Brigade of the Knights of the First Winter Campaign (Armed Forces of Ukraine) – Serhii Belinskyi.